Optimisation of chlorine disinfection in drinking water supply network - Rozman, Urška (Sanitarno inženirstvo, 2022)
Chlorination is one of the most commonly used procedures for drinking waterdisinfection. The research aimed to soptimise the subsequent disinfection ofdrinking water with chlorine in the water supply network in the city Velenje,taking into account the applicable legislation. The gradual reduction of chlorinedosage was implemented with simultaneous monitoring of selected physico-chemical and microbiological parameters of drinking water. During the two-month period, 418 samples were taken at 22 previously defined differentsampling spots. Free chlorine values were reduced from the initial 0,18 mg/L tothe final 0,08 mg/L at the outlet, while values at some remote sampling sitesreached only 0,01 mg/L of free chlorine. Microbiological analyses of samplesshowed that the drinking water met the limit values in the regulations, despitethe low values of free chlorine. Based on the results, a modified chlorination ofdrinking water was introduced in the tested supply area, and the introduction ofa similar regime in other supply areas is being actively considered. In this way,we reduce the consumption of disinfectants and ensure the supply of qualityand healthy drinking water to consumers.
Keywords: mikrobiološki parametri; optimizacija kloriranja; pitna voda; Slovenija - Velenje